Synthesis and characterization of epoxidized neem oil: A bio‐derived natural processing aid for elastomer. Issue 20 (6th January 2021) - Koley, Riya; Kasilingam, Rajkumar; Sahoo, Suchismita; Chattopadhyay, Santanu; Bhowmick, Anil K.
Abstract: Low cost and environment‐friendly bio‐oils are gaining market value as a plasticizer for elastomeric compounds. Unsaturated triglycerides of bio‐oils can be easily modified in various ways, like epoxidation, esterification, and so on. In the present work, 15 mole percentage of the total double bond content of the neem oil (NO) was epoxidized by acetic acid‐hydrogen peroxide system to synthesize epoxidized neem oil (ENO). NO and ENO were characterized by nuclear magnetic resonance spectroscopy, Fourier transform infrared spectroscopy and differential scanning calorimetry. The effect of ENO on the properties of nonpolar styrene butadiene rubber (SBR) and polar nitrile rubber (NBR) was investigated. Tear strength (69.9 N/mm), abrasion resistance index (ARI) (68.2) and hardness (64 shore A) of the SBR/ENO compound were comparable to the compound containing total distillate aromatic extract (TDAE) (values: 70.8 N/mm, 68.0 and 64 shore A respectively). Tensile strength and ARI of conventional NBR/dioctyl phthalate (DOP) compound were 24.9 MPa and 107 respectively, whereas NBR/ENO compound showed improved tensile strength (26.9 MPa), and ARI (138). Tear strength (83.4 N/mm) and hardness (74 shore A) of NBR/ENO were comparable to the tear strength (83.5 N/mm) and hardness (74 shore A) of NBR/DOP compound. Hence, the multifunctional additive property of ENO makes it a cheap and sustainable replacement of TDAE and DOP. Abstract :